MINAT DAN MOTIVASI MAHASISWA UNTUK MENJADI WIRAUSAHAWAN MUDA MANDIRI (Studi pada Mahasiswa Universitas Borobudur Angkatan 2015) - Sri Sungkowati (Fakultas Ekonomi Universitas Borobudur, 2017)
This research was conducted with the aim to know the interest and motivation of students of Universitas Borobudur to become Young Entrepreneurs Mandiri. 100 students of Borobudur University Force 2015 became Respondents in this study. Data collection using questionnaires. The sample technique used in this research is Proportionate Stratified Random Sampling. This research belongs to descriptive research. Descriptive analysis will also be given to explain cross tabulation tables. The results showed that students of the University of Borobudur force in 2015 as a whole have been interested to become Young Entrepreneurs Mandiri, which amounted to 95.4%. With the following details: students who are interested and have their own business of 16.9%, students who are already interested and running a business but failed 14.6%, and there are 63.9% of students who are interested to become Young Entrepreneurs Mandiri, but have not started yet. While not yet interested there is still 4.6%. Other results found that the motivation of students of Borobudur University class of 2015 to become Independent Young Entrepreneurs included in the high category, the average total score reached 73.63%. The motivation of students of Universitas Borobudur to become Young Entrepreneurs Mandiri on average is to have their own business, want to implement their idea and innovate and want to earn better income or income. Keywords: Entrepreneurship, Interest in Entrepreneurship, Entrepreneurship Motivation, Student